Margaret C. Flinn. The Social Architecture of French Cinema, 1929-1939. Liverpool: Liverpool UP, 2014. - Hazel Hahn (Studies in 20th & 21st Century Literature, 2016)
Review of Margaret C. Flinn. The Social Architecture of French Cinema, 1929-1939. Liverpool: Liverpool UP, 2014.
Keywords: French cinema; architecture; 1930s; spatial theory